Development and research of system descriptions of architecture processors is with address access in the base of Galois - Humenniy, Petro (Видавництво Львівської політехніки, 2010)
This research shows, that possibilities of VIT using makes possible to decrease structure and algorithmic complication to a few degrees. As a consequence such devices will have higher speed and more reliability. Possibility of such special processors and memory devices in view of discrete PLIS crystals realization and massive use of them in computer and telecommunication systems.
Keywords: vertical-information technology (VIT) microchip; microprocessor; microelectronics; ROM; Ram